Hill politics in Northeast India - "Chaube, S.K." (Hyderabad, 2012)
Since the middle of the nineteenth century, the northeast has grown from ethnocentric tribal organisations to territorial autonomous structures through a profound process of change in all spheres of life and society led by an educated and sophisticated middle class the third, revised edition of hill politics in northeast india, traces the political evolution of the region, excluding sikkim, from the first half of the eighteenth century when british administration was formally set up in assam to the twenty-first century this volume looks at how many of the political concerns that continue to plague the region till today have their roots in the past it, however, also contends that while historical problems remain, there has been increasing awareness and interaction between the people of the northeast and the rest of india this thoroughly revised edition includes updated text and tables that will help readers gain a holistic view of the politics of the hills in the twenty-first century the book will be of particular interest to students and scholars of political science, sociology and history it will also be useful for administrators and lay readers who are interested in the northeast
Keywords: "India, Northeastern-Politics"